The influence of additional absorption on the acoustical indicators of a hall/Papildomos absorbcijos įtaka salės modelio akustiniams rodikliams - Stauskis, Vytautas (Journal of Civil Engineering and Management, 1998)
The influence of the slits between the walls and the floor of the model upon the objective acoustical indicators was examined in a scaled model of a hall. The Small Hall of the Lithuanian National Philharmonic Society was selected for the investigations. The hall is of rectangular form, 13.6 m in length, 10.7 m in width and 7 m in height. The hall model was scaled 1:25. The floor and the ceiling of the model were made of cloth-based laminate, while the walls of plywood 8 mm thick, with three layers of varnish. Thus, all materials employed in the model were similar to those of the real hall by their sound-absorption properties. There were 1 to 3 mm slits between the floor and the walls of the model. Their overall length was about 10–12 m (converted to real values). A spark sound source was used for the radiation of signals within the required spectrum. The sound source was put through a hole in the floor in order to improve the directivity diagram of the radiation. The positions of both the source and the ¼ microphone coincided in all cases. The frequencies examined fell in the range between 1250 Hz and 50000 Hz. The frequency of quantization of the signal was 166.6 kHz and the quantization time was 6 mcs. All frequencies were converted into real ones in the diagrams. A 2000 Hz upper limit was established to ensure that the Nyquist frequency exceeds 3. The experiments showed that the slits in the model influenced the muffling of the sound energy starting from 200 ms. With the slits present, the muffling occurs faster and the greatest difference of 2–3 dB is observed in the interval of 1000–2500 ms. Given small slit dimensions and overall slit length, the change of 2–3 dB is quite significant. The muffling of the sound field of the model is not exponent in character. The muffling varies on differently in different time intervals. Then the reverberation times of a non-filtered signal must be different when the muffling is approximated every 10 dB. The investigation showed that, with the slits present, the reverberation time values were reduced by 0.4–0.8 s throughout the interval when the muffling was approximated every 10 dB, starting from 0 to – 30 dB and from – 5 to – 35 dB. This means that the slits absorb the sound energy on all intervals of the muffling of the sound field. The largest sound absorption is reached when the muffling of the sound field is approximated every 10 dB from 0 to – 30 dB and amounts to as much as 3–6 m2. The influence of the slits is weaker when the muffling is approximated on other intervals. The slits also produce effect upon subjective acoustical indicators of a non-filtered signal, which vary between 1 to 2 dB. This shows that the intensity of reflections is changed in various time intervals by the slits. The influence exerted by the slits over the early reverberation time manifests itself both at the low and high frequencies. The greatest difference of about 0.8 s is observed at 100 Hz and 160 Hz. Within the frequency range from 500 Hz to 1000 Hz, the difference is not so marked and amounts to about 0.5 s. Within the range from 200 Hz to 400 Hz, the early reverberation time is only slightly influenced by the slits. The effect produced by the slits on the standard reverberation time, as compared with the early reverberation time, is not significant up to 160 Hz, while in the frequency range of 200—2,000 Hz the standard reverberation time is cut by about 0.4–0.6 s. The smallest sound absorption brought about by the slits is observed at low frequencies (around 1 m2). In the frequency range of 200—500 Hz, the sound absorption amounts to 3–4 m2, and at the frequencies exceeding 630 Hz to 2–7 m2. At low frequencies, the music sound clarity index is increased by the slits by about 0.5 dB. From 200 Hz and on, the clarity index is increased by 2 to 4 dB. These results show that the slits in the model alter the intensity of the early sound reflections. Beginning with 250 Hz, the sound absorption amounts to 3.2–9.0 m2. Such absorption is already significant, therefore the slit factor must be taken into consideration while conducting investigations in the hall model.Article in Lithuanian.First Published Online: 26 Jul 2012